National, longitudinal NASCITA birth cohort study to investigate the health of Italian children and potential influencing factors. Issue 11 (15th November 2022) - Pandolfini, Chiara; Clavenna, Antonio; Cartabia, Massimo; Campi, Rita; Bonati, Maurizio
Abstract : Purpose: The NASCITA Study, a national-level, population-based, prospective cohort study, was set up to better understand the early health status of Italian children, comprising their physical, cognitive and psychological development, and how it is affected by social and health determinants, including nurturing care. NASCITA will also assess geographical differences and disparities in healthcare. Participants: Participating family paediatricians from throughout Italy enrolled infants born during the enrolment period (April 2019–July 2020). The 5054 newborns seen by the 139 paediatricians for at least two visits, including the first well-child visit, and for whom parental consent was given, make up the baseline population. Findings to date: Mothers had a mean age at delivery of 33.0 years and tended to have a high or medium level of education (42.5% university and 41.7% high school degrees) and to be employed (69.7%). One-third (36.1%) took folic acid supplementation appropriately, and 6.5% smoked or consumed alcohol (10.0%) during pregnancy. One-third (31.7%) of deliveries were caesarean deliveries. Concerning the newborns, 5.8% had a low birth weight and 6.2% were born prematurely. The majority (87.7%) slept in the supine position, and 63.6% were exclusively breast fed at 1 month, with a decreasing north to south prevalence (χ 2 t 52; p<0.001). Significant north–south differences were found in all areas, including parental education, behaviours in pregnancy and hospital practices. When compared with national level data, the cohort population's distribution, maternal sociodemographic characteristics and newborn physical characteristics reflect those of the Italian population. Future plans: Data will continue to be collected during the well-child visits until the children are 6 years old, and multiple health outcomes will be studied, spanning child development and illness, as well as potentially related factors including caregiving routines. The findings will be used to develop specific interventions to improve children's health. Trial registration number: NCT03894566 .